The Hiang Thian Siang Ti Temple, July 2017 - Universiti Malaysia Sarawak, Faculty of Social Science (Faculty of Social Science, 2017)
The Hiang Thian Siang Ti Temple is one of the popular temples in Kuching for photographer and researcher. Shown is the Penang famous photographer and traditional architect Mr Tan Yeow Wooi, taking building photos of the temple in (July 2017), observed by a local Chinese Study Anthropologist/Researcher, Dr Elena Chai Chin Fern.